Analysis of possible intoxications resulting from the indiscriminate use of ivermectin and hydroxychloroquine during the COVID-19 pandemic (Research, Society and Development, 2022)
Introduction: In late December 2019, there was an outbreak of an emerging disease (COVID-19) due to a new coronavirus, called SARS-CoV-2, which started in Wuhan, China, spreading globally as a pandemic. The critical scenario imposed by has driven the search for therapeutic and prophylactic pharmacological strategies, such as ivermectin and hydroxychloroquine. Objective: to highlight, through empirical and current analyses, the risks associated with the indiscriminate use of ivermectin and hydroxychloroquine as therapeutics against COVID-19, highlighting the toxicity effects of these drugs. Methodology: this is a descriptive research of the integrative literature review type. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases. Information Services, in August 2021. Results and discussion: according to ANVISA, there are still no conclusive studies that accept the hypothesis that ivermectin is effective in the treatment of COVID-19. As for hydroxychloroquine, in relation to its mechanism of action, hydroxychloroquine is believed to act, under COVID-19 infection, by preventing terminal glycosylation of the ACE2 enzyme, which, in turn, acts as a membrane receptor for SARS- CoV-2, which can then prevent the virus from binding. However, there is still no dispute about the effectiveness of these drugs under COVID-19, and there are even reports of organic toxicity related to the indiscriminate use of these drugs, associated with problems such as bleeding, renal failure, arrhythmias and even drug hepatitis. Final considerations: the role of the physician and, even more, the clinical pharmacist, is of paramount importance, which goes beyond the pharmacotherapeutic follow-up to patients who use polypharmacy.